2020
DOI: 10.1186/s13287-020-01726-3
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell-derived lung alveolar epithelial type II cells reduce damage in bleomycin-induced lung fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis is a chronic, progressive, and severe disease with a limited response to currently available therapies. Epithelial cell injury and failure of appropriate healing or regeneration are central to the pathogenesis of idiopathic pulmonary fibrosis. The purpose of this study is to investigate whether intratracheal transplantation of alveolar type II-like cells differentiated from induced pluripotent stem cells can stop and reverse the fibrotic process in an experimental mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Previously, Serrano-Mollar et al demonstrated, in preclinical studies, that AE2C intratracheal transplantation was able to reduce fibrosis and restore pulmonary surfactant proteins levels ( 18 , 19 ). They also observed that the induced pluripotent stem cells (iPSCs) derived AE2C reduce fibrosis by inhibiting TGF-β and α-SMA expression ( 23 ). Furthermore, in a clinical study performed with IPF patients, the intratracheal administration of heterologous AE2C was safe, well-tolerated and with no relevant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Serrano-Mollar et al demonstrated, in preclinical studies, that AE2C intratracheal transplantation was able to reduce fibrosis and restore pulmonary surfactant proteins levels ( 18 , 19 ). They also observed that the induced pluripotent stem cells (iPSCs) derived AE2C reduce fibrosis by inhibiting TGF-β and α-SMA expression ( 23 ). Furthermore, in a clinical study performed with IPF patients, the intratracheal administration of heterologous AE2C was safe, well-tolerated and with no relevant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In general, obtaining and maintaining MSCs in cell culture is much easier compared to ATII [ 62 , 63 ]. MSCs can be isolated from several adult tissues and from fetal tissues, while ATII cells are acquired from an adult´s healthy donor lungs or can be derived in vitro from pluripotent cells [ 35 , 62 ]. Due to the MSC immune-privileged behavior, it is possible an autologous or allogenic treatment that avoids the use of immunosuppression in patients [ 16 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are easier to obtain than ATII, which need to be isolated from healthy death lung donors. Nowadays, ATII can also be obtained by the differentiation of adult pluripotent cells in vitro [ 31 , 32 , 33 , 34 , 35 ]. Both cell types were tested in clinical trials for several lung diseases, with a good safety record in patients [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technical problems, such as high individual treatment doses (e.g., several million cells/kg) and treatment administration logistics have been reported, limiting the easy and widespread use of such approaches [83,84]. Noteworthy alternatives yet parallel approaches to stem or progenitor cell therapy consist of the functional restoration of normal resident lung progenitor cells (e.g., ATII cells) using various approaches or the therapeutic use of induced pluripotent stem cell (iPSC) technology for the management of diverse lung injuries (e.g., caused by chemical aggression or hyperoxia) [100][101][102][103].…”
Section: Potential Therapeutic Applications Of Diploid Lung Progenitors In Respiratory Tract Regenerative Medicinementioning
confidence: 99%